Sexual Orientation and the Law: Valid and Valuable Jurisprudence - Becker, Susan J. (Columbia Journal of Gender and Law, 2000)
The thesis of this essay is that sexual orientation and the law is a legitimate course to offer in law schools and an appropriate topic for scholarly endeavor as well. I would expect the reader to be somewhat confounded by this thesis. Isn’t this settled already? Certainly a significant number of law schools regularly offer courses related to this area. Law reviews and journals, including specialty ones such as the one containing this essay, devote pages and even entire volumes to literature on sexual orientation and gender. Law schools and other institutions routinely sponsor symposia and conferences dedicated to unraveling the myriad of legal, political, religious, economic, and social dimensions of sexual orientation. All this is true, of course. But there is a swirling undercurrent, a backlash perhaps, that cannot be ignored. Since I started teaching law in 1990, and became seriously committed to my identity as a life-long student of the law as well as a law teacher and a legal scholar, I have received less- than-enthusiastic feedback on my plan to produce scholarship on sexual orientation issues. Somewhat surprisingly, this reaction came not from colleagues aligned on the right side of the political spectrum, but rather from some of my more liberal colleagues who are wholly supportive of the extension of basic legal rights and remedies to gays and lesbians.